Chemical protein synthesis: total synthesis of proteins for biological research - Kent, Stephen (Henry Stewart Talks, 2008)
HIV-1 protease, Electronic properties of the catalytic apparatus, Defining the 'aspartyl proteases', 'Backbone engineering' HIV-1 PR, The alpha-helix, Ubiquitin (76 aa), Conformation vs. solvation effects, Global and local structures are highly conserved, Stability measurements of [Aaa35] ubiquitins, Energetic contributions at helix C' position, Erythropoietin (Epo), Synthetic erythropoiesis protein, Synthetic 'glycan mimetic', Glycoprotein synthesis, Molecular basis of protein function, The synthetic challenge, Classical solution synthesis, Stepwise solid-phase synthesis, Chemical protein synthesis, Unprotected peptides, Principles of chemical ligation, Thioester-forming ligation, Total synthesis of D- & L-HIV-1 protease, Crystal structure of D-HIV-1 protease, Native chemical ligation, Crambin (46 aa; 6 Cys), CPS: current challenges
Archived at 2020/08/13